Măsuri de ocupare pe piața muncii a persoanelor cu dizabilități - Arpinte, Daniel (Calitatea Vieții, 2014)
The article aims to investigate the potential of support measures for the integration on the labour market of people with disabilities, and to identify both the main weaknesses of these measures and the proposals that might be implemented in order to increase the efficiency of the support system. The article shows that the quota system for employment is inefficiently implemented in Romania and does not have the expected impact for the used resources. Although there are favourable legislative and fiscal provisions supporting the integration on the labour market, only 4.7% of the people with disabilities are employed. Therefore, the inefficiency of the employment policies is obvious, along the lack of interest of the in charge public institutions and the inefficiency in using the European funds targeting the integration of the people with disabilities on the labour market. The article ends with a few proposals for increasing the efficiency of quota system for employment and for the additional specific measures, like the development of a system for subsidies for adapting the working places, extending the compulsory contribution to the protection of the disabled people for employers with less than 50 employers, improving the efficiency for the implementation of the legal provisions related to the disabled people protection, implementation of special fund fed by the tax of 50% by gross minimum wage for each job which is not held by a disabled person, developing employment programs for disabled people on the labour market, helping sheltered workshops for providing support for inclusion of disabled people on the labour market, increasing the quota of disabled people in total employers for sheltered workshops from 30% to 50%.